Evaluation of the Compliance of Orthodontists to Infection Control Procedures in Turkey - Asuman Deniz Gümrü Çelikel; Hasan Ekmekçioğlu; Güven Külekçi; Sönmez Fıratlı (Galenos Yayinevi, 2018)
Objective:Orthodontists do not perform surgical procedures, nevertheless they are obliged to practice appropriate sterilization techniques to prevent cross-infection. This is also important from an ethical and legal point of view. The aim of the present study is to evaluate the compliance of orthodontists to infection control procedures in Turkey.Methods:A questionnaire with 36 items was delivered by e-mail to a total of 1152 orthodontists/residents between October 2014 and March 2015 by the Turkish Orthodontic Society. Various data from surveys were analyzed using the IBM SPSS statistics 22 software.Results:The questionnaire was completed by 130 (11.28%) respondents. 95.4% of the orthodontists were immunized against hepatitis B. The usage rates of type B autoclave, non-type B autoclave, and dry-heat sterilizer were 40%, 17.7%, and 16.9%, respectively. A total of 24.6% of the orthodontists used disinfectant solutions for the sterilization of hand instruments and pliers; the rate of using disinfectants for the sterilization of dental handpieces was found to be higher (56.9%).Conclusion:The infection control procedures in the field of orthodontics must be improved in Turkey. Training on compliance with the infection control principles should be included in education programs, and these programs should be repeated on a regular basis.